TEACHER'S PERSPECTIVES TOWARD GOOGLE CLASSROOM AS A TOOL FOR IMPROVING ELT CLASSROOM INTERACTION - Imam Tyas Sansinadi; Winarko Winarko (Getsempena English Education Journal, 2020)
Google Classroom as a tool that connects teachers and students which encourage interaction with each other through a virtual online class that offers various features. This study was conducted to investigate the effects of using Google Classroom in the ELT class for improving classroom interaction through the teacher's perspectives. By using the phenomenological qualitative research with a sample of one private junior high school teacher in Yogyakarta, data collected were obtained using open-ended and semi-structured interviews. The analysis was done by reading each transcript, rereading, and looking for common words that fit the category. The result revealed that the use of Google Classroom in ELT class is beneficial in the learning process, it can increase students' attention. However, some students did not pay attention to the learning process, and the students used English to communicate if the teacher asked them in the learning process.